El comportamiento del consumidor de las plazas de mercado de Villavicencio, Meta (2018)
Market squares are one of the most beneficial sectors for the country, given that they satisfy first category needs and contribute to the region’s economy, which is why its preservation and analysis is important for said sector. The present article is the analysis of consumer behavior in the market squares, in the city of Villavicencio where there is a fairly notorious trade in fruit and vegetables in the country, from where they are supplied to towns. As a result of a theoretical and practical investigation, where information was collected on consumer purchasing statistics, in different markets and under different items and circumstances, the information gathered was analyzed and results yielded are observed at the end of this article, as well as the conclusions made on what was observed in the field work developed for this research.